(±)-Bicoryanhunine A, dimeric benzylisoquinoline alkaloid atropo-enantiomers from Corydalis yanhusuo. Issue 21 (21st May 2020) - Xiao, Biao-Bing; Xia, Gui-Yang; Wang, Ling-Yan; Qiu, Bo-Lin; Xia, Huan; Zhong, Wan-Chao; Tian, Gui-Hua; Lin, Sheng
Graphical abstract: Highlights: A pair of dimeric benzylisoquinoline alkaloid atropo -enantiomers was isolated from Corydalis yanhusuo . Isolation by chiral-phase HPLC. A moderate PD-1/PD-L1 interaction inhibitor. Abstract: Bicoryanhunine A (1 ), isolated from the dried tubers of Corydalis yanhusuo, is the first novel dimeric benzylisoquinoline alkaloid with a 4, 7′-coupled biaryl axis. This novel C-4-C-7′ linkage lead to the highest steric hindrance at the biaryl axis, giving rise to a pair of atropo -enantiomers that are well resolved into the anticipated enantiomers, (+)-bicoryanhunine A (1 ) and (−)-bicoryanhunine A (1 ), with the help of chiral-phase HPLC. Their structures including the axial configurations were elucidated by spectroscopic methods and experimental and calculated ECD investigations. Bicoryanhunine A (1 ) was a moderate PD-1/PD-L1 interaction inhibitor with an IC50 value of 14.3 ± 0.67 μM.